Isotope hydrogeology and aqueous geochemistry of selected British Columbia hotsprings. - Phillips, Robert John. (University of Ottawa (Canada), 1994)
Hydrogeochemical analyses of the thermal waters at Hotsprings Cove, west coast Vancouver Island, reveal the presence of a stable geothermal reservoir. Temperature (50.5$\sp\circ$C), and aqueous geochemical data are nearly identical to those dating back to 1898. $\delta\sp $O-D plots indicate local recharge for these thermal waters, whereas radiocarbon isotopes suggest mean residence times of several thousand years and modification by sulphate-reducing bacteria. Bromide/chloride ratios, when considered with tritium and $\sp{34}$S data, are indicative of minor seawater mixing near the discharge zone. Binary mixing models, with local recharge waters and local seawater as end-member components, point to maximum local seawater contributions of about 1% and 4% for Hotsprings Cove and associated Mate Island thermal waters, respectively. Most chemical and isotopic geothermometer estimates are 90$\sp\circ$C. The Ahouset hotspring, located 12 km south of Hotsprings Cove has low total dissolved solids, a pH of 10.05, and a different geochemistry. Data from the Selkirk Range show a consistent sodium-sulphate geochemistry among the three hotsprings sampled in the Kuskanax Batholith. All waters have low bicarbonate content. $\sp $C values in excess of 100 pmc at the Nakusp hotspring imply incorporation of $\sp $C-active DIC from soil zone organics entrained during recharge, with possible additional $\sp $C contributions occurring due to sulphate reduction and incorporation of soil zone organics during mixing with non-thermal groundwaters near discharge. $\sp $C-derived mean residence times for the sulphide-rich waters of Halcyon hotspring are also short; possibly ${\sim}$1000 years. Geothermometer estimates for all three springs are consistent and fall into two groups, one group near ${\sim}$90$\sp\circ$C and the other between 115$\sp\circ$C and 155$\sp\circ$C. (Abstract shortened by UMI.)
Keywords: Geology.